An Analysis of Thermal Comfort Models: Which One Is Suitable Model to Assess Thermal Reality in Brazil? - Iasmin Lourenço Niza; Evandro Eduardo Broday (Energies, 2022)
The Predicted Mean Vote (PMV) has discrepancies in relation to the thermal reality of the environment; thus, adaptive models serve to improve this estimate. In this context, this research aimed to verify the performance of PMV and adaptive models under different conditions in Brazil from an analysis of variance and to further classify individuals into clusters according to their feelings of thermal comfort. Through ASHRAE’s Global II Thermal Comfort Database, users of offices and classrooms in Brasilia, Recife, Maceió, and Florianópolis were investigated. The results of ANOVA showed that the PMV model did not represent the thermal reality of any of the cities investigated, and the cluster analysis showed how most people felt thermally in relation to indoor environments.